1966
DOI: 10.4315/0022-2747-29.3.88
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Raw Milk From Selected Ohio Markets.

Abstract: Summary An 8-month survey was made on the flavor of raw milk supplies from four major Ohio markets. A total of 317 milk samples obtained from farm bulk tanks and from tank trucks were examined fresh and after storage at 38–40 F for 48 hours. Approximately 40% of the industrial producer's fresh milk supply had highly satisfactory flavor quality and the flavor of 10% of the shipments was completely undesirable. The combining of the producers' milk in the tank pick-up truck resulted in milk for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1971
1971
1978
1978

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The major effect of this change has been to reduce the quantity of milk spoiled by souring which occurred when it was produced under poor conditions of hygiene and inadequately cooled. Unfortunately the introduction of refrigerated cooling and storage has not removed spoilage defects in raw milk supplies; an investigation by Ohri & Slatter (1966) of milk from farm tanks revealed that 10 per cent of the milk on arrival at the depots had undesirable flavours. These undesirable flavours which have been variously described as unclean, fruity, rancid, bitter and even putrid are largely due to the hydrolytic activities of psychrotrophic micro-organisms on milk fat and protein.…”
Section: Refrigerated Storage Of Raw Pilkmentioning
confidence: 99%
“…The major effect of this change has been to reduce the quantity of milk spoiled by souring which occurred when it was produced under poor conditions of hygiene and inadequately cooled. Unfortunately the introduction of refrigerated cooling and storage has not removed spoilage defects in raw milk supplies; an investigation by Ohri & Slatter (1966) of milk from farm tanks revealed that 10 per cent of the milk on arrival at the depots had undesirable flavours. These undesirable flavours which have been variously described as unclean, fruity, rancid, bitter and even putrid are largely due to the hydrolytic activities of psychrotrophic micro-organisms on milk fat and protein.…”
Section: Refrigerated Storage Of Raw Pilkmentioning
confidence: 99%